Association of COMT Val158Met Polymorphism with Fibromyalgia in Khartoum State, Sudan - Safaa Mamoun Abdelmageid; Faisal Mousa Alamir; Hassan Yousif Abdelrahman; Hind Mohamed Abushama (Pain Research and Management)
Fibromyalgia (FM) is a disorder characterized by chronic musculoskeletal pain, fatigue, and cognitive problems. Neurotransmitters, mainly catecholamines, appear to be involved in regulating the etiology of FM. Catechol-O-methyltransferase (COMT) is involved in catabolizing catecholamines such as norepinephrine. The most common variant studied in the COMT gene is the valine (Val) to methionine (Met) substitution at codon 158. This is the first study in Sudan addressing FM cases and genetic susceptibility to the disease. We aimed in this study to investigate the frequency of COMT Val 158 Met polymorphism among patients with FM, rheumatoid arthritis, and in healthy individuals. Genomic DNA from forty female volunteers was analyzed: twenty were from primary and secondary FM patients, ten were from rheumatoid arthritis patients, and ten were from healthy control. FM patients’ age was ranging from 25 years to 55 with a mean of 41.14 ± 8.90. The mean age of the rheumatoid arthritis patients and healthy individuals was 31.3 ± 7.5 and 38.6 ± 11.2, respectively. Samples were genotyped for COMT single nucleotide polymorphism rs4680 (Val158Met), using the amplification-refractory mutation system (ARMS-PCR). Genotyping data have been analyzed using the Chi-square and Fisher exact test. The most common genotype among the study participants was the heterozygous Val/Met found in all participants. It was the only genotype found in the healthy participants. The genotype Met/Met was found only in FM patients. The genotype Val/Val was found only in rheumatoid patients. Analyses have shown no association between the Met/Met genotype and FM, and this could be due to a small sample size. In a larger sample size, a significant association could be found as this genotype was shown only by FM patients. Moreover, the Val/Val genotype, which is shown only among rheumatoid patients, might protect them from developing FM symptoms.